Ultrahigh-temperature micro-ablation material and preparation method thereof
By introducing ultra-high temperature ceramics into the C/C blank and using multi-component structure and pioneer impregnation and cracking (PIP) densification method, the problem of oxidation of C/C composite materials in high temperature environments is solved, and ultra-high temperature micro-ablation materials with excellent mechanical and ablation resistance are prepared, which are suitable for high-temperature application conditions.
Patent Information
- Application Number
- CN202510008038.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-03
AI Technical Summary
The existing C/C composite materials are prone to oxidation in high temperature environments, resulting in significant reduction in mechanical properties and service life, and cannot meet the high-temperature application conditions of devices such as aircraft engines and automobile brake discs.
By modifying the internal modification of the C/C blank, ultra-high temperature ceramics such as SiC, HfC, ZrC, TaC and HfB2, ZrB2, TaB2 are introduced to form a multi-component structure. The coating preparation method is adopted, including atmospheric pressure natural impregnation, physically assisted vibration impregnation and pioneer impregnation cracking (PIP) density to prepare ultra-high temperature microablation materials with excellent mechanical properties and ablation resistance.
It achieves good ablation resistance of ultra-high temperature microablizers at high temperatures of 2300℃, while maintaining excellent mechanical properties, avoiding damage to carbon fibers, and is suitable for industrial production.
Smart Images

Figure CN119775041A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic-based composite materials, and in particular relates to an ultra-high temperature micro-ablation material and a preparation method thereof. Background Art
[0002] C / C composite material is a carbon-based composite material with carbon fiber as reinforcement. It not only has the excellent mechanical properties of fiber-reinforced materials, but also has many advantages of carbon materials, such as low density, low thermal expansion coefficient, high thermal conductivity and electrical conductivity, excellent thermal shock resistance, ablation resistance and friction resistance, etc. It has become an ideal structural material in the fields of aerospace, automobile, medicine, etc.
[0003] However, C / C composite materials will be oxidized at about 400℃ in the air, and the mechanical properties and service life of C / C composite materials will be significantly reduced after oxidation. The operating temperature of components such as aircraft engines and automobile brake discs reaches above 1400℃. Obviously, the existing C / C composite materials cannot meet the use conditions. How to further improve the ablation resistance of C / C composite materials in high temperature environments and improve the high temperature application environment of C / C composite materials is still the focus and difficulty of current and future research.
[0004] Modifying the matrix of C / C composites and using ultra-high temperature ceramic matrices such as ultra-high temperature carbides and borides instead of carbon matrix can significantly improve the ablation resistance and mechanical properties of C / C composites, and meet the service conditions of key components such as aircraft nose cones, wing leading edges, and hot ends of aircraft engines in extreme environments. Ultra-high temperature carbides have high melting points, high strength, high hardness, and good chemical stability. Currently, the commonly used carbide ultra-high temperature ceramics are mainly SiC, HfC, ZrC, and TaC. Their melting points are much higher than their oxides, and they do not need to undergo any solid phase transitions. They can maintain good strength and thermal shock resistance at high temperatures; ultra-high temperature borides mainly include HfB2, ZrB2, and TaB2. Thanks to the strong covalent bonds in the boride structure, they have the characteristics of high melting points, high strength, high hardness, low evaporation rate, high thermal conductivity, and high electrical conductivity. Compared with C / (C-)Hf(Zr)C-SiC, C / (C-)SiC-Hf(Zr)B2 composite materials have good oxidation resistance in a wider temperature range. This is mainly because when oxidized at a relatively low temperature of 800℃~1000℃, a large amount of boron oxide can be generated on the surface of the material. In a medium temperature oxidation environment of 1000℃~1700℃, borosilicate and SiO2 liquid phase will be generated on the surface of the material, and at a high temperature of 1700℃~2200℃ (or even higher), SiO2 will be formed on the surface of the material. 2-ZrO2 solid solution and solid phase ZrO2 stable glass phase. In order to make the material have good ablation resistance in a wider temperature range, it is necessary to add multiple components to toughen and strengthen the material and improve its anti-oxidation and anti-ablation capabilities through multi-component synergy.
[0005] At present, the methods for preparing multi-element ultra-high temperature ceramic matrix modified C / C composites at home and abroad mainly focus on Precursor Infiltration and Pyrolysis (PIP) and Reaction Metl Infiltraction (RMI).
[0006] The document [“Preparation of compact ZrC-SiC ceramic matrix from thermosetprecursors for C / C-ZrC-SiC composites with high mechanical properties. Mingdong Liao a, Manuel Reyes De Guzman b, GuoboShen, etl. Journal of theEuropean Ceramic Society, 44 (2024) 1983-1999”] discloses a method for preparing a C / C-Zr -SiC composite material with a dense ceramic matrix by precursor infiltration and pyrolysis. They believe that the dense structure of the ZrC-SiC ceramics prepared by this method is attributed to the tightly cross-linked structure, which can be directly crystallized without carbon thermal reduction. The precursor structure after pyrolysis is denser, the generated ceramic matrix is denser, and the interface bonding between the ceramic matrix and the carbon matrix is better. The composite material has a dense ZrC-SiC matrix and a slightly defective interface, and has an ideal non-brittle fracture mode. The ZrC-SiC matrix has a high elastic modulus, while moderate thermal residual stress damage and interface bonding lead to obvious crack deflection and fiber pullout. However, the precursor impregnation and cracking process requires repeated impregnation and cracking. During the cracking process, the matrix is prone to shrinkage and defects, resulting in a decrease in the mechanical properties of the material.
[0007] The literature [“Ultra-high-temperature ablation behavior of SiC-ZrC-TiCmodified carbon / carbon composites fabricated via reactive metl infiltration.Yi Zeng, Dini Wang, Xiang Xiong eatl. Journal of European Ceramic Society, 40(2020)651-659”] uses reactive solution infiltration to prepare SiC-ZrC-TiC ternary ceramic matrix on C / C composite. This ceramic matrix is composed of Zr-rich and Ti-rich solid solution Zr1−xTixC and SiC. They believe that the good ablation resistance of C / C-SiC-ZrC-TiC composites is mainly due to the multiphase oxide layer on the surface of the composite material. By providing low volatility and high viscosity oxides, the multiphase oxide layer has strong resistance to high temperature volatility and high-speed airflow scouring. However, this method requires high temperature conditions and is relatively energy-consuming. In addition, during the preparation process, the molten metal will react with the carbon fiber to cause fiber damage, and the unreacted metal inside the material will accelerate creep and destroy phase equilibrium in the high-temperature environment of service, thereby reducing the material performance. Summary of the invention
[0008] In view of the deficiencies in the prior art, the first object of the present invention is to provide a method for preparing an ultra-high temperature micro-ablation material. The present invention adopts a multi-component structure with a coating, and the preparation process is simple and controllable, which is suitable for industrial production.
[0009] The second object of the present invention is to provide an ultra-high temperature micro-ablation material prepared by the above-mentioned preparation method, wherein the ultra-high temperature micro-ablation material has a high volume fraction of ultra-high temperature ceramics, a uniform organizational structure, excellent mechanical properties, antioxidant properties, and anti-ablation properties, can withstand high-temperature ablation at 2300°C, and can maintain good mechanical properties during the ablation process.
[0010] In order to achieve the above object, the present invention provides the following technical solutions: The invention discloses a method for preparing an ultrahigh temperature micro-ablation material. The method comprises the following steps: modifying the interior of a C / C body to obtain a modified C / C body, placing the modified C / C body in a slurry containing ultrahigh temperature ceramics, and sequentially subjecting the body to natural impregnation at normal pressure, physical assisted vibration impregnation, and drying to obtain a C / C-ultrahigh temperature ceramic matrix composite body; and then densifying the C / C-ultrahigh temperature ceramic matrix composite body through precursor infusion pyrolysis (PIP) to obtain an ultrahigh temperature micro-ablation material.
[0011] The preparation method of the present invention first performs internal modification of the C / C blank, weakens the friction resistance between the fiber and the ceramic powder, increases the effect of chemical bonding, and then achieves high-content introduction of ultrahigh temperature ceramic powder by modifying the capillary force of the C / C blank itself and auxiliary vibration operation, forming a dual-continuity and uniform distribution of UHTCs and carbon fibers, and obtains a C / C-ultrahigh temperature ceramic-based composite blank after impregnation and drying, and then prepares a silicon carbide matrix by impregnation and low-temperature (~1300°C) cracking and densification, and simultaneously fixes and wraps the ultrahigh temperature ceramic powder to obtain a C / C-multi-component ultrahigh temperature ceramic-based composite material. The preparation method of the present invention can effectively avoid damage to the carbon fiber and ensure that the C / C-multi-component ultrahigh temperature ceramic-based composite material has excellent mechanical properties and ablation resistance.
[0012] In a preferred embodiment, the density of the C / C body is 0.45-0.70 g / cm 3 .
[0013] In a preferred embodiment, the C / C blank is obtained by depositing a pyrolytic carbon coating on a carbon fiber preform by chemical vapor infiltration (CVI), and the thickness of the pyrolytic carbon coating is 200-400 nm.
[0014] Further preferably, the carbon fiber preform is selected from one of a needle-punched preform (2.5D fabric) and a fine-woven puncture preform (3D fabric).
[0015] Further preferably, the density of the carbon fiber preform is 0.40-0.65 g / cm 3 .
[0016] Further preferably, the carbon fiber preform is firstly heat treated at 1600-2000° C. under argon protection, and then subjected to chemical vapor infiltration (CVI) to deposit the pyrolytic carbon coating.
[0017] In a preferred embodiment, the process of internal modification of the C / C body is as follows: firstly, the C / C body is placed in an oxidant for oxidation etching, then the oxidized and etched C / C body is immersed in a solution containing a modifier for hydrolysis reaction, and then dried to obtain the product, wherein the modifier is selected from a silane coupling agent and / or polyacrylic acid.
[0018] Further preferably, the oxidant is selected from one of HNO3 solution, H3PO4 solution and KMnO4 solution, preferably HNO3 solution, in which the mass fraction of HNO3 is 30-65%.
[0019] Further preferably, the oxidation etching temperature is 50-60° C. and the time is 1-2 h.
[0020] Further preferably, the oxidation etching treatment is performed under the assistance of ultrasound. In order to better allow the ultra-high temperature powder to be uniformly introduced into the interior of the modified C / C body, the oxidation etching treatment is performed under the assistance of ultrasound, so that the interior of the C / C body can be fully and uniformly oxidized and etched, thereby promoting uniform modification of the modifier.
[0021] Further preferably, the solution containing the modifier consists of ethanol, water, and the modifier, and the mass ratio of ethanol: water: modifier is 9-12: 1: 0.02-0.15.
[0022] In the present invention, a solution containing a modifier is prepared using a mixed solvent of ethanol and water, wherein the proportion of each component must be effectively controlled. If there is too little water, the modifier cannot be fully hydrolyzed; if there is too much water, the modifier is over-hydrolyzed before it combines with the fiber surface; too much or too little water is not conducive to the combination of the modifier with the fiber surface.
[0023] More preferably, the silane coupling agent is selected from at least one of γ-aminopropyltriethoxysilane (KH-550), γ-aminopropyltrimethoxysilane (A-1110), and γ-mercaptopropyltriethoxysilane (KH-580).
[0024] Further preferably, the hydrolysis reaction temperature is 70-80°C and the time is 1-2h.
[0025] Further preferably, the hydrolysis reaction is carried out under ultrasound assistance. The inventors have found that the modification process can be more uniform under ultrasound. If it is not carried out under ultrasound, the modification process is uneven, which affects the distribution of the ultra-high temperature ceramic powder inside the green body.
[0026] In a preferred embodiment, the ultra-high temperature ceramic-containing slurry comprises ultra-high temperature ceramic powder, a dispersant, and a solvent.
[0027] Further preferably, the slurry containing ultra-high temperature ceramics also contains silicon carbide powder.
[0028] Further preferably, the ultra-high temperature ceramic powder in the ultra-high temperature ceramic-containing slurry is selected from at least two of zirconium boride, hafnium boride, zirconium carbide, hafnium carbide, and lanthanum boride powders; preferably zirconium carbide and hafnium carbide, and the particle size of the ultra-high temperature ceramic powder is 0.2-0.7 μm.
[0029] The inventors found that at least two ultra-high temperature ceramic powders need to be used. If only one of them is selected, the synergistic effect between the ultra-high temperature ceramic components and between the ultra-high temperature ceramic components and SiC cannot be fully exerted. On the one hand, the oxide skeleton formed by the oxidation of the ultra-high temperature ceramic components can stabilize the ablation surface and play a role in resisting ablation. On the other hand, the borosilicate formed by the oxidation of SiC, SiO2 alone or with B2O3 formed by the oxidation of boride, can play a role in filling the liquid phase oxide film. The synergistic effect between at least two ultra-high temperature ceramic powders can make the ablation surface of the material consist of a stable ultra-high temperature oxide solid skeleton and a liquid oxide film.
[0030] In addition, the particle size of the ultra-high temperature ceramic powder needs to be effectively controlled within the range of the present invention so that it can be uniformly introduced into the interior of the C / C body.
[0031] Further preferably, the volume fraction of the ultra-high temperature ceramic powder in the ultra-high temperature ceramic slurry is 10-40 vol.%.
[0032] The ultra-high temperature ceramic slurry provided by the present invention has a high solid content and low viscosity. The ultra-high temperature ceramic slurry of the present invention is combined with natural impregnation at normal pressure and physically assisted vibration impregnation to introduce ultra-high temperature ceramics with a volume fraction greater than 20 vol.% into ultra-high temperature micro-ablation materials. By regulating the ratio and content of ultra-high temperature ceramic powder in the slurry, the content and type of ultra-high temperature ceramic components in the C / C-ultra-high temperature ceramic-based composite material can be adjusted over a wide range, and the dual continuous distribution of ceramic phase and fiber, the continuous component content and the continuous spatial distribution can be achieved, thereby improving the ablation resistance of the composite material at a high temperature of 2300°C.
[0033] Further preferably, the dispersant is selected from one or two of polyethyleneimine, polyvinyl butyral, ammonium citrate, polyethylene glycol, polycarbosilane, and hydrogenated styrene-butadiene block copolymer.
[0034] Further preferably, the added amount of the dispersant is 8-20% of the mass of the ultra-high temperature ceramic powder.
[0035] The inventors found that by controlling the amount of dispersant added within the preferred range, the pH value of the ultra-high temperature ceramic slurry can be adjusted without adjusting the pH value, that is, the ceramic powder can be evenly dispersed in the slurry. If the amount of dispersant added is too much, the ceramic powder surface will be grafted with excessive dispersant, agglomerate, and affect dispersion and introduction into the green body; if the amount of dispersant added is too little, the ceramic powder will be unevenly dispersed and easily precipitate, and it will not be able to maintain a stable state within the experimental time, affecting impregnation.
[0036] Further preferably, the solvent is one or two of deionized water, anhydrous ethanol, acetone, and xylene.
[0037] Further preferably, the preparation process of the ultra-high temperature ceramic slurry is: prepare ultra-high temperature ceramic powder, silicon carbide powder, dispersant, and solvent according to the designed proportion, and then ball milling, the ball milling speed is 180-220r / min, and the ball milling time is 2-3h.
[0038] Preferably, the mass ratio of the grinding balls to the ultra-high temperature ceramic powder is 2-4:1.
[0039] The preparation method provided by the present invention changes the surface properties of the C / C blank through modification treatment, weakens the friction resistance between the fiber and the ceramic powder, and increases the effect of chemical bonding. The ultra-high temperature ceramic matrix can be introduced into the blank by impregnation with the ultra-high temperature ceramic slurry at room temperature and pressure. There is no need to adjust the pH value of the ultra-high temperature ceramic slurry during the preparation process. Only by adjusting the amount of the dispersant, the preparation of the ultra-high temperature ceramic slurry with high solid content and low viscosity can be achieved, and a high content of ultra-high temperature ceramic components can be introduced. The ceramic matrix and the carbon fiber are evenly distributed in two phases, and no damage is caused to the silicon carbide fiber. On the premise of ensuring the mechanical properties of the material, the ablation resistance of the composite material at a high temperature of 2300°C can be improved.
[0040] In a preferred embodiment, the time for the natural impregnation at normal pressure is 60-90 minutes.
[0041] In a preferred embodiment, the vibration frequency of the physical assisted vibration impregnation is 800-1500 times / min, and the physical assisted vibration impregnation time is 30-60 min. In the actual operation process, the physical vibration assistance is achieved by using a physical assisted vibration impregnation instrument.
[0042] In the present invention, after the C / C body is modified and pretreated, and the slurry is reasonably prepared, the pretreated C / C body only needs to be naturally immersed in the slurry at normal pressure for 60-90 minutes, and then physically assisted by vibration for 30-60 minutes to complete the immersion. The assisted vibration can realize the dense stacking of ceramic particles and improve the actual volume ratio of ceramic entering the C / C body. The manufacturing process of the present invention is efficient, easy to operate, and does not damage the fiber.
[0043] In the present invention, natural impregnation is performed first, and the slurry can be absorbed into the deep of the green body by the capillary action of the green body itself; during natural impregnation, in addition to ceramic powder, there is also solvent in the internal voids of the green body, and the powder does not fully fill the pores; physical assisted vibration impregnation can make the powder in the pores stack tightly, fill the pores as much as possible, and increase the amount of ceramic powder introduced. However, it is necessary to first naturally impregnate at normal pressure for 60-90 minutes before physically assisted vibration impregnation can be performed. Physical assisted vibration is performed too early, which will cause bridge-type blockage of the powder in the pores during the impregnation process, blocking the pores and affecting the subsequent introduction of the matrix, resulting in poor impregnation effect and uneven dispersion of ceramic powder in the green body.
[0044] In a preferred embodiment, the drying temperature is 80-100° C. and the drying time is 1.5-8 hours.
[0045] In the present invention, the drying can be carried out by freeze drying, vacuum drying oven or conventional drying oven.
[0046] In a preferred embodiment, the density of the C / C-ultra-high temperature ceramic matrix composite material is 0.9-3.2 g / cm 3 .
[0047] In a preferred embodiment, the process of precursor impregnation cracking and densification is as follows: the C / C-ultra-high temperature ceramic matrix composite material is impregnated in an impregnating agent, firstly vacuum impregnated, and then pressurized impregnated. After the impregnation is completed, the composite material is solidified and cracked, and then the impregnation-solidification-cracking is repeated until the composite material is dense. The impregnating agent is selected from a PCS-xylene solution or a liquid polycarbosilane. In the PCS-xylene solution, the mass ratio of PCS:xylene is 0.5-1:0.5-1.
[0048] Further preferably, the vacuum impregnation time is ≥4 h, and the pressure of the pressurized impregnation is 2.7-3 MPa and the time is 8-10 h.
[0049] More preferably, the curing temperature is 110-220° C. and the curing time is 4-5 hours.
[0050] In a further embodiment, the cracking temperature is 1000-1300°C, the cracking time is 0.5-1h, and the heating rate is 2-10°C / min.
[0051] In a preferred embodiment, the surface of the ultra-high temperature ceramic substrate obtained by densifying the ultra-high temperature micro-ablation material through precursor infusion pyrolysis (PIP) is coated with a surface coating, and the ultra-high temperature micro-ablation material is obtained after drying.
[0052] Further preferably, the coating used for painting comprises an anti-oxidation coating prepared from Er-Y-Ls rare earth powder and SiC whiskers.
[0053] The present invention also provides an ultra-high temperature micro-ablation material prepared by the above-mentioned preparation method, wherein the ultra-high temperature micro-ablation material comprises carbon fiber, pyrolytic carbon wrapped around carbon fiber, an ultra-high temperature ceramic matrix, and a SiC matrix. The ultra-high temperature ceramic in the ultra-high temperature ceramic matrix is selected from at least two of zirconium boride, hafnium boride, zirconium carbide, hafnium carbide, and lanthanum boride, preferably zirconium carbide and hafnium carbide.
[0054] Further preferably, the density of the ultra-high temperature micro-ablation material is 2.8 g / cm 3 -3.5g / cm 3, bending strength is 200-330MPa, fracture toughness is 8.19-42.13MPa·m 1 / 2 The line ablation rate in 2300K oxyacetylene is 0.06-0.56μm / s, and the mass ablation rate is 0.26-1.92mg / s.
[0055] Principles and advantages The present invention prepares ultra-high temperature ceramic slurry with high solid content and low viscosity, utilizes the capillary force of the C / C blank itself and auxiliary vibration operation, realizes the introduction of ultra-high temperature ceramic powder in a large range, forms a dual-continuity and uniform distribution of UHTCs and carbon fiber, and then uses the PIP process after drying to repeatedly impregnate and solidify the SiC matrix through low-temperature (~1300°C) cracking and densification, and simultaneously fixes and wraps the ultra-high temperature ceramic powder to obtain an ultra-high temperature micro-ablative material. The preparation method of the present invention can effectively avoid damage to the carbon fiber and ensure that the ultra-high temperature micro-ablative material has excellent mechanical properties and ablation resistance.
[0056] The method of the ultra-high temperature ceramic matrix introduced in the present invention will not damage the fibers, and the matrix is evenly distributed. The composite oxide film generated in situ by the multiphase ceramic matrix during the ablation process has high integrity, and can achieve both anti-oxidation and anti-ablation effects through synergistic action. The complete and tough oxide layer effectively blocks the loss of liquid-phase oxides, so that the material does not crack when flushed by high-temperature and high-speed airflow. The coupling effect of multiple toughening mechanisms such as crack deflection, crack bifurcation, fiber bridging, bundled fiber pull-out and interface debonding during the fracture process well maintains the non-brittle fracture characteristics of the material.
[0057] By controlling the ratio of the ultra-high temperature ceramic slurry and the number of cycles of polymer impregnation and cracking, the components and content of the ultra-high temperature ceramic matrix in the material can be controlled, thereby achieving control over the microstructure and properties of the material.
[0058] Compared with the reaction infiltration method and the needle injection method of ultra-high temperature ceramic slurry, the method of the present invention can introduce ultra-high temperature ceramic components at low temperature without damaging the carbon fiber, and the carbon fiber reinforcement effect is preserved.
[0059] The ultra-high temperature micro-ablation material prepared by the present invention has excellent anti-ablation performance, and also has the advantages of high strength and corrosion resistance. The linear ablation rate of the Cf / HfC-ZrC-SiC composite material in the 2300K oxyacetylene experiment is only 0.06μm / s. During the ablation process, the HfC-ZrC-SiC composite ceramic matrix can in-situ generate a composite oxide film composed of liquid SiO2 and solid HfO2, and the synergistic effect of the two can achieve both anti-oxidation and anti-ablation effects.
[0060] In summary, the production process of the present invention is simple and easy to control, the preparation cost is low, and it is suitable for industrial production. The C / C-multi-component ultra-high temperature ceramic matrix composite material prepared by the present invention has controllable microstructure and performance, uniform organization, high strength, and excellent high temperature resistance, corrosion resistance, and ablation resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 The surface of the Cf / HfC-ZrC-SiC composite material after ablation in Example 1; Figure 2 The surface center morphology of the Cf / HfC-ZrC-SiC composite material after ablation in Example 1; Figure 3 Surface transition region morphology of the Cf / HfC-ZrC-SiC composite material after ablation in Example 1; Figure 4 XRD spectrum of the Cf / HfC-ZrC-SiC composite material in Example 1. DETAILED DESCRIPTION
[0062] The present invention will be further described below with reference to examples.
[0063] Example 1 A method for preparing an ablation-resistant and high-temperature-resistant ceramic matrix composite material is provided, and the preparation steps are as follows: Step 1: Carbon fiber pretreatment and surface deposition of carbon coating: with a density of 0.40 g / cm 3 The 2.5D needle-punched carbon felt was used as the preform and heat treated at 1800°C in an argon atmosphere with a heating rate of 10°C / min and a holding time of 1h. A pyrolytic carbon interface layer was deposited on the debonded carbon fiber preform with propylene as the carbon source gas for 35h to obtain a C / C blank containing a PyC layer, in which the thickness of the PyC layer was 300nm.
[0064] Step 2, C / C body modification: The low-density body obtained in step (2) is immersed in a dilute nitric acid solution and subjected to ultrasonic oxidation etching at 50°C for 1 hour, dried at 80°C, and then modified using a mixed solution of ethanol and water containing silane coupling agent KH-550, wherein the mass ratio of ethanol: water: silane coupling agent KH-550 in the solution containing the modifier is 12:1:0.15, and ultrasonic hydrolysis reaction is carried out at 80°C for 1 hour, and dried at 80°C to obtain a surface-modified C / C body.
[0065] Step 3, the modified C / C body is compounded with an ultra-high temperature ceramic slurry: polyethyleneimine (PEI) is used as a dispersant to prepare an aqueous solution containing the dispersant, and then HfC, ZrC, and SiC powders are added to the aqueous solution containing the dispersant, and ball milled in a planetary ball mill for 3 hours to prepare a HfC-ZrC-SiC water-based ceramic slurry with a solid content of 35 vol%, the amount of the dispersant added is 20wt% of the total mass of the powder, and the average particle size of the HfC, ZrC, and SiC powders is 500nm, and the surface-modified C / C body in step 2 is immersed in the configured HfC-ZrC-SiC water-based ceramic slurry and naturally immersed at normal pressure for 60 minutes, and then physically assisted vibration immersed for 30 minutes; during the physically assisted vibration immersed, the vibration frequency is 1400 times / min, and the moisture in the three-dimensional needle-punched integral felt after impregnation is removed, and the drying temperature is 100°C for 8 hours.
[0066] Step 4, densification of C / C-ultra-high temperature ceramic matrix composite material: placing the C / C-green body containing HfC-ZrC-SiC obtained in step 3 in a high-pressure impregnation kettle, filling the pores in the green body with polycarbosilane (PCS) by pressure impregnation, and then placing the impregnated green body in a vacuum cracking furnace for cracking to obtain a carbon fiber reinforced carbon and hafnium carbide-zirconium carbide-silicon carbide matrix (C / C-HfC-ZrC-SiC) composite material. During PIP densification, polycarbosilane is used as a raw material, xylene is used as a solvent, the mass ratio of PCS to xylene is 1:1, the pressure of pressurized impregnation is 3MPa, the pressurized impregnation time is 8 hours, and then it is cured at 220°C for 5 hours, and then the C / C-HfC-ZrC-SiC composite material is vacuum cracked at 1200 for 30 minutes, and the cycle is repeated until the weight gain rate of the sample before and after is ≤1%, so as to obtain a dense C / C-HfC-ZrC-SiC composite material; the obtained C / C-HfC-ZrC-SiC composite material has a volume ratio of 27.59% after slurry impregnation into ceramics, and a density of 3.02g / cm after densification. 3 .
[0067] The test results show that the C / C-HfC-ZrC-SiC composite material obtained in this embodiment has a bending strength of 323.00 MPa and a fracture toughness of 42.13 MPa·m 1 / 2 In the 2300K oxyacetylene experiment, the line ablation rate was 0.06μm / s and the mass ablation rate was 0.26mg / s.
[0068] Example 2 The difference between this embodiment and embodiment 1 is that in step 3, polyethyleneimine (PEI) is used as a dispersant and ethanol is used as a solvent to obtain an ethanol solution containing the dispersant. There is no need to adjust the pH of the solvent. Then, HfB2, ZrB2, and SiC powders are added to the ethanol solution containing the dispersant, and ball milled in a planetary ball mill for 3 hours to prepare a HfB2-ZrB2-SiC ceramic slurry with a solid phase content of 28 vol%. The amount of the dispersant added is 12 wt% of the total mass of the powder, and the average particle size of the HfB2, ZrB2, and SiC powders is 500 nm.
[0069] The volume ratio of the obtained C / C-HfB2-ZrB2-SiC composite material after slurry impregnation into ceramic is 15.11%, and the density is 2.89g / cm 3 .
[0070] The test results show that the C / C-HfB2-ZrB2-SiC composite material obtained in this embodiment has a bending strength of 235.49 MPa and a fracture toughness of 8.19 MPa·m 1 / 2 In the 2300K oxyacetylene experiment, the line ablation rate was 0.53μm / s and the mass ablation rate was 0.87mg / s.
[0071] Embodiment 3: The difference between this embodiment and embodiment 1 is that in step 3, polycarbosilane (PCS) and hydrogenated styrene-butadiene block copolymer are used as dispersants, and the two are dissolved in xylene to obtain a PCS-SEBS-xylene solution with a concentration of 0.8 g / mL, and then HfC, LaB6, and SiC powders are added to the solution, and ball milled in a planetary ball mill for 3 hours to prepare a HfC-LaB6-SiC water-based ceramic slurry with a solid content of 25 vol%, and the average particle size of the HfC, LaB6, and SiC powders is 500 nm.
[0072] The volume ratio of the obtained C / C-HfC-LaB6-SiC composite material after slurry impregnation into the ceramic is 16.95%, and the density is 3.44g / cm 3 .
[0073] The test results show that the C / C-HfC-LaB6-SiC composite material obtained in this embodiment has a bending strength of 208.09 MPa and a fracture toughness of 18.43 MPa·m 1 / 2 In the 2300K oxyacetylene experiment, the line ablation rate was 0.33μm / s and the mass ablation rate was 1.92mg / s.
[0074] Embodiment 4: The difference between this embodiment and embodiment 1 is that in step 3, polyethyleneimine (PEI) is used as a dispersant, which is added into water to obtain an aqueous solution containing the dispersant, and then ZrB2, ZrC, and SiC powders are added into the aqueous solution containing the dispersant, and the mixture is ball-milled in a planetary ball mill for 3 hours to prepare a ZrB2-ZrC-SiC water-based ceramic slurry with a solid phase content of 35 vol%. The amount of the dispersant added is 13% of the total mass of the powder, and the average particle size of the ZrB2, ZrC, and SiC powders is 500 nm.
[0075] The volume ratio of the obtained C / C-ZrB2-ZrC-SiC composite material after slurry impregnation into ceramic is 27.73%, and the density is 2.88g / cm 3 .
[0076] The test results show that the C / C-ZrB2-ZrC-SiC composite material obtained in this embodiment has a bending strength of 280.00 MPa and a fracture toughness of 31.03 MPa·m 1 / 2 In the 2300K oxyacetylene experiment, the line ablation rate was 0.56μm / s and the mass ablation rate was 0.80mg / s.
[0077] Comparative Example 1 The difference between this comparative example and Example 1 is that the low-density green body obtained in step 1 is immersed in dilute nitric acid (concentration) for oxidation etching treatment for 2 hours, and then immersed in polyethylene glycol solution, water and temperature 80°C, ultrasonic for 1 hour, and dried at 80°C for 2 hours to completely evaporate the solvent to obtain a surface-modified C / C green body.
[0078] In step 3, polyethyleneimine (PEI) is added to water as a dispersant to obtain an aqueous solution containing the dispersant, and the pH value of the aqueous solution containing the dispersant is adjusted to 7 using acetic acid and ammonia water. Then, HfC, ZrC, and SiC powders are added to the aqueous solution containing the dispersant, and ball-milled in a planetary ball mill for 3 hours to prepare HfC-ZrC-SiC water-based ceramic slurry, and the average particle size of the powder is 500 nm.
[0079] In this comparative example 1, the carbon fiber was modified without depositing a carbon coating on the surface after pretreatment. The slurry prepared by adjusting the pH value could not penetrate the C / C body well. Some slurries were severely stratified after standing for half an hour after the ball milling, causing the powder to form a crust on the surface and causing a large concentration gradient on the inner and outer surfaces, resulting in uneven powder impregnation, which affected the composite effect of the modified C / C body and the ultra-high temperature ceramic slurry, and failed to successfully prepare the composite material.
[0080] Comparative Example 2 This comparative example is different from Example 1 in that: The low-density green body obtained in step 1 was immersed in H3PO4 or KMnO4 solution for ultrasonic oxidation etching for 1 hour, and then immersed in silane coupling agent KH-550 modifier, ultrasonic hydrolysis reaction at room temperature or below 30°C for 1 hour, and dried at 80°C until the solvent is completely volatilized to obtain a modified C / C green body. White precipitate was observed on the surface of the green body. The reason is that the silane coupling agent is over-hydrolyzed or the hydrolysis temperature is too low, the silane coupling agent forms an overpolymer or precipitates from the solution, resulting in uneven modification inside the green body, so that the ultra-high temperature ceramic slurry cannot penetrate into the green body well.
[0081] Comparative Example 3 This comparative example is different from Example 1 in that: In the slurry prepared in step 4, the ultra-high temperature ceramic powder is only one of HfC, ZrC, ZrB2, and HfB2.
[0082] The performance test results of the ultra-high temperature ceramic matrix composite material prepared in this comparative example are as follows:
[0083] It can be seen from the above results that when the ultra-high temperature ceramic phase is a single component, the mechanical properties and ablation resistance of the material are reduced, which is obviously not as good as the performance of the C / C-multi-component ultra-high temperature ceramic-based composite in Example 1.
[0084] Comparative Example 4 This comparative example is different from Example 1 in that in step 3, polyethyleneimine (PEI) is added to water as a dispersant to obtain an aqueous solution containing the dispersant, and the amount of the dispersant added is 5wt% or 25wt% of the total mass of the powder. Then, HfC, ZrC, and SiC powders are added to the aqueous solution containing the dispersant, and ball milled in a planetary ball mill for 3h to prepare a HfC-ZrC-SiC water-based ceramic slurry, and the average particle size of the powder is 500nm.
[0085] In this comparative example 4, when the amount of dispersant added was 5wt% of the total mass of the powder, the dispersant in the slurry could not be fully combined with the ceramic powder, causing the powder to form a crust on the surface, and causing a large concentration gradient between the inner and outer surfaces, resulting in uneven powder impregnation, reducing the composite effect of the modified C / C green body and the ultra-high temperature ceramic slurry, and failing to successfully prepare a composite material. When the amount of dispersant added was 25wt% of the total mass of the powder, the viscosity of the prepared slurry increased, the fluidity deteriorated, the ceramic slurry formed a crust on the surface of the green body, and the green body and the slurry were not successfully composited.
[0086] Comparative Example 5 The difference between this comparative example and Example 1 is that the surface-modified C / C body in step 2 is immersed in the prepared HfC-ZrC-SiC water-based ceramic slurry and naturally immersed for 30 minutes at normal pressure, and then physically assisted by vibration and immersed for 60 minutes. The volume ratio of the obtained C / C-HfC-ZrC-SiC composite material entering the ceramic after slurry immersion is 11.01%. Compared with Example 1, the volume ratio of ceramic entering is greatly reduced. Obviously, the internal pores of the body are not fully filled, the ceramic matrix is unevenly distributed, and the slurry immersion effect is poor.
Claims
1. A method for preparing an ultra-high temperature micro-ablation material, characterized in that: The internal part of a C / C body is modified to obtain a modified C / C body, and the modified C / C body is placed in a slurry containing ultra-high temperature ceramics and impregnated naturally at normal pressure, impregnated physically with vibration, and dried to obtain a C / C-ultra-high temperature ceramic matrix composite material; and the C / C-ultra-high temperature ceramic matrix composite material is densified by impregnation and cracking of a precursor to obtain an ultra-high temperature micro-ablation material.
2. The method for preparing an ultra-high temperature micro-ablation material according to claim 1, characterized in that: The density of the C / C body is 0.45-0.70 g / cm 3 ; The C / C blank is obtained by depositing a pyrolytic carbon coating on a carbon fiber preform through chemical vapor infiltration, and the thickness of the pyrolytic carbon coating is 200-400 nm; The carbon fiber preform is selected from a needle-punched preform and a fine-woven puncture preform; The density of the carbon fiber preform is 0.40-0.65 g / cm 3 ; The carbon fiber preform is firstly heat treated at 1600-2000° C. under argon protection, and then chemical vapor infiltration deposition pyrolytic carbon coating is performed.
3. The method for preparing an ultra-high temperature micro-ablation material according to claim 1, characterized in that: The process of modifying the interior of the C / C body is as follows: firstly, the C / C body is placed in an oxidant for oxidation etching, then the oxidized C / C body is immersed in a solution containing a modifier for hydrolysis reaction, and then dried to obtain the C / C body, wherein the modifier is selected from a silane coupling agent and / or polyacrylic acid; The oxidant is selected from one of HNO3 solution, H3PO4 solution and KMnO4 solution; The oxidation etching temperature is 50-60°C and the time is 1-2h; The oxidation etching process is performed under the assistance of ultrasound; The solution containing the modifier is composed of ethanol, water and the modifier, and the mass ratio of ethanol: water: modifier is 9-12: 1: 0.02-0.15; The silane coupling agent is selected from at least one of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane and γ-mercaptopropyltriethoxysilane; The temperature of the hydrolysis reaction is 70-80°C and the time is 1-2h; The hydrolysis reaction is carried out under the assistance of ultrasound.
4. The method for preparing an ultra-high temperature micro-ablation material according to claim 1, characterized in that: The ultra-high temperature ceramic slurry comprises ultra-high temperature ceramic powder, a dispersant, and a solvent; The ultra-high temperature ceramic-containing slurry further comprises silicon carbide powder; The ultra-high temperature ceramic powder in the ultra-high temperature ceramic slurry is selected from at least two of zirconium boride, hafnium boride, zirconium carbide, hafnium carbide, and lanthanum boride powders; The particle size of the ultra-high temperature ceramic powder is 0.2-0.7 μm; The volume fraction of the ultra-high temperature ceramic powder in the ultra-high temperature ceramic slurry is 10-40 vol.%; The dispersant is selected from one or two of polyethyleneimine, polyvinyl butyral, ammonium citrate, polyethylene glycol, polycarbosilane, and hydrogenated styrene-butadiene block copolymer; The amount of the dispersant added is 8-20% of the mass of the ultra-high temperature ceramic powder; The solvent is one or two of deionized water, anhydrous ethanol, acetone and xylene.
5. The method for preparing an ultrahigh temperature micro-ablation material according to claim 1 or 4, characterized in that: The preparation process of the ultra-high temperature ceramic slurry is as follows: ultra-high temperature ceramic powder, silicon carbide powder, dispersant and solvent are prepared according to the designed proportion, and then ball milled, the speed of the ball mill is 180-220r / min, and the ball milling time is 2-3h; The mass ratio of the grinding balls to the ultra-high temperature ceramic powder is 2-4:
1.
6. The method for preparing an ultrahigh temperature micro-ablation material according to claim 1, characterized in that: The time of natural impregnation at normal pressure is 60-90 minutes; During the physical assisted vibration impregnation, the vibration frequency is 800-1500 times / min, and the physical assisted vibration impregnation time is 30-60min; The drying temperature is 80-100° C., and the drying time is 1.5-8 hours.
7. The method for preparing an ultrahigh temperature micro-ablation material according to claim 1, characterized in that: The process of precursor impregnation cracking and densification is as follows: impregnating the C / C-ultra-high temperature ceramic matrix body into an impregnating agent, first performing vacuum impregnation, and then performing pressure impregnation. After the impregnation is completed, the body is solidified and cracked to obtain the product; the impregnating agent is selected from a PCS-xylene solution or liquid polycarbosilane, and in the PCS-xylene solution, the mass ratio of PCS to xylene is 0.5-1:0.5-1; The vacuum impregnation time is ≥4h, and the pressure of the pressurized impregnation is 2.7-3MPa and the time is 8-10h; The curing temperature is 110-220°C and the curing time is 4-5h; The cracking temperature is 1000-1300° C., the cracking time is 0.5-1h, and the heating rate is 2-10° C. / min.
8. The method for preparing an ultrahigh temperature micro-ablation material according to claim 1, characterized in that: The surface of the ultra-high temperature ceramic matrix obtained by impregnating and cracking the C / C-ultra-high temperature ceramic matrix composite material with a precursor is coated with a surface coating, and the ultra-high temperature ceramic matrix composite material is obtained after drying; The coating used for painting comprises an anti-oxidation coating prepared from Er-Y-Ls rare earth powder and SiC whiskers.
9. The ultra-high temperature micro-ablation material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The ultra-high temperature micro-ablation material comprises carbon fiber, pyrolytic carbon wrapped in carbon fiber, an ultra-high temperature ceramic matrix, and a SiC matrix. The ultra-high temperature ceramic in the ultra-high temperature ceramic matrix is selected from at least two of zirconium boride, hafnium boride, zirconium carbide, hafnium carbide, and lanthanum boride.
10. The ultra-high temperature micro-ablation material according to claim 9, characterized in that: The density of the ultra-high temperature micro-ablation material is 2.8 g / cm 3 -3.5g / cm 3 , bending strength is 200-330MPa, fracture toughness is 8.19-42.13MPa·m 1 / 2 The line ablation rate in 2300K oxyacetylene is 0.06-0.56μm / s, and the mass ablation rate is 0.26-1.92mg / s.
Citation Information
Patent Citations
Preparation method of carbon / carbon-boron nitride anti-friction composite material
CN109665855A
Ultrahigh-temperature ceramic-based composite material and preparation method thereof
CN112521157A
Ultrahigh-temperature ceramic modified C / C composite material for aerospace power and preparation method of ultrahigh-temperature ceramic modified C / C composite material
CN119080524A
Secondary battery
KR1020250137229A
Long-term ablation-resistant nitrogen-containing carbide ultra-high temperature ceramic with ultra-high melting point and application thereof
US20220009838A1
Cited By
Tungsten alloy material containing silicon carbide reinforced Al2O3-SiO2-based multiphase ceramic coating and preparation method of tungsten alloy material
CN120556016A